The moderating effects of perceived intentionality: exploring the relationships between ideas of reference, paranoia and social anxiety in schizotypy - Morrison, Sean C.; Cohen, Alex S. (Cognitive neuropsychiatry, 2014)
Introduction. Ideas of reference (IOR), paranoia and social anxiety are features of schizophrenia-spectrum disorders, which appear to be conceptually related; however, the precise nature of these relationships is unclear. These relationships may be partially explained by perceived intentionality (PI), a social-cognitive bias for perceiving other people's actions during unpleasant situations as being directed at oneself in an intentionally malicious manner. Our primary aim was to examine the moderating role of PI on the relationships between IOR and paranoia, and between IOR and social anxiety amongst individuals with psychometrically defined schizotypy. Methods. We assessed IOR, paranoia and social anxiety amongst individuals with psychometrically defined schizotypy (n = 44) and controls (n = 36) and examined the moderating effects of PI within each group. Results. As hypothesised, PI moderated the relationship between IOR and paranoia such that higher PI predicted higher levels of paranoia as IOR increased. Additionally, we found that PI moderated the relationship between IOR and social anxiety such that higher PI predicted lower levels of social anxiety as IOR increased. Conclusion. Theoretical and practical implications are discussed including the potential for assessing PI as a proxy for paranoia when clinicians suspect a client is underreporting paranoia due to positive impression management.